Sexually-transmitted infections: what is the true prevalence? A cross-sectional online survey of men who have sex with men in the Veneto Region of Italy - Pierbon, M; Cocchio, S; Russo, C; Bonamin, M A; Baldo, V (Journal of preventive medicine and hygiene, 2019)
Rates of sexually-transmitted infections (STIs) remain high among men who have sex with men (MSM), posing serious public health concerns. The MSM population is recognized as a vulnerable, high-risk group due to barriers to preventive healthcare services and homophobic stigma. A cross-sectional online survey was conducted using a questionnaire based on European Man-for-Man Internet Survey 2010 (EMIS 2010) and European Centre for Disease Prevention and Control (ECDC) core indicators specific for behavioral risks. MSM were reached between June and August 2017, using Facebook and dating apps. Descriptive statistics and multivariate logistic regression were used to analyze the data. A total of 324 respondents were analyzed, 88 subjects (27.2% of the sample) reported having experienced at least one STI, the most common being gonorrhea and HPV. Ten respondents reported having HIV infection, and 7 subjects (70%) of them were co-infected with other STIs. The 49.7% (161 subjects) had seen a doctor specifically for STIs. As concerns HPV vaccination, only 4.0% of the total respondents had been vaccinated. Restricting the sample to the 161 respondents who consulted an STI clinic, the 88 individuals who reported having had at least one STI amount to 54.6%. A more consistent use of condoms and larger numbers of sexual partners were significantly associated with a lower and higher risk of STI, respectively. Comprehensive STI prevention strategies are needed to improve sexual health among MSM. Such strategies should include implementing programs to improve awareness about routine screening, and promote a consistent use of condoms by MSM.